Race, equity, and public schools in post-apartheid South Africa: is opportunity equal for all kids? - Yamauchi, Futoshi (International Food Policy Research Institute, 2004)
This paper examines dynamic changes in educational quality and equity differences in the public school system between Black and other racial groups in post-apartheid South Africa, using the ratio of learners to educators in each school, available from the School Register of Needs, 1996 and 2000. The analysis incorporates school- and community-level unobservables and the endogenous movement of learners. This paper shows that (1) the learner-educator ratios significantly differ between formerly Black and White primary and secondary schools in 1996 and 2000, and (2) in the adjustment of educators in response to changes in the number of learners in this period, there are significant differences between formerly Black and non-Black (White, Coloured, and Indian) primary schools. The opportunities for education in public schools are still unequal between Black and White children, even after apartheid. Given that school quality affects returns to schooling and earning opportunities in labor markets, the inequality causes income inequality between Black and White. The empirical result calls for stronger policy intervention to support Black schools and children in South Africa. -- Author's Abstract